RETRACTED: Media Pembelajaran dan Peran Pentingnya dalam Pengajaran dan Pembelajaran Bahasa Arab - Ibnu Mas'ud Luthfi (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2023)
RETRACTED: Following a rigorous, carefully concerns and considered review of the article published in Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab to article entitled “Media Pembelajaran dan Peran Pentingnya dalam Pengajaran dan Pembelajaran Bahasa Arab” Vol 1, No 1, pp. 8-16, December 2023, DOI: https://doi.org/10.61181/jilunaarabiyah.v1i1.352. This paper has been found to be in violation of the Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Al-Fusha: Arabic Language Education Journal, Vol 2 No 2, Juli (2020), pp. 63-77, DOI: https://doi.org/10.36835/alfusha.v2i2.358, entitled